The Effect of Organizational Climate on Work Motivation and Its Impact on Organizational Citizenship Behavior (OCB) of Employees of Education Department in DKI Jakarta - Arnest Sinaga; Thamrin Abdullah; Billy Tunas (Journal of Business and Behavioural Entrepreneurship, 2019)
The objectives of this research was to study the effect of organizational climate on work motivation and its impact on organizational citizenship behavior (OCB) of Education Department employees in Province of DKI Jakarta. Quantitative approach used in this research with survey method. The samples of this research were 120 people selected randomly. The data were obtained by distributing questionnaire and analyzed by using path analysis. The first results of the research can be concluded that organizational climate and work motivation had a positive direct effect on OCB. Second, organizational climate had a positive direct effect on work motivation. Third, organizational climate had a positive indirect effect on OCB through work motivation as an intervening variable. Therefore to improve OCB of Education Department employee in Province of DKI Jakarta, then organizational climate and work motivation should be improved.